2013
DOI: 10.4012/dmj.2012-262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marginal failures of dental composite restorations by acoustic emission analysis

Abstract: In this study, a nondestructive method based on acoustic emission (AE) analysis was developed to evaluate the marginal failure states of dental composite restorations. Three types of ring-shaped substrates, which were modeled after a Class I cavity, were prepared from polymethyl methacrylate, stainless steel, and human molar teeth. A bonding agent and a composite resin were applied to the ring-shaped substrates and cured by light exposure. At each time-interval measurement, the tooth substrate presented a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Different methods of composite evaluation success and functioning conditions are continuously developing and improving. Except for the used clinical criteria, techniques, such as spectrometric analyses or acoustic emission analysis, could be effectively implemented into clinical practice for the purpose of non-destructive composite restorations evaluation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Different methods of composite evaluation success and functioning conditions are continuously developing and improving. Except for the used clinical criteria, techniques, such as spectrometric analyses or acoustic emission analysis, could be effectively implemented into clinical practice for the purpose of non-destructive composite restorations evaluation [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…. However, these methods only provide post-evaluation of the interface after debonding has already occurred by polymerization shrinkage stress.Recent studies using this technique have confirmed that a slower rate of polymerization [57] , better bonding surface, low-shrinkage composites, and lower C-factor [58,59,60,61] , are strongly associated with better resistance to interfacial debonding as evidenced by fewer Acoustic emission analysis (AE) events.The high-viscosity bulk-fill composites may not have advantages over the high-viscosity conventional composite. In contrast, compared with the low-viscosity conventional composite, the low-viscosity bulk-fill composites showed better performance in terms of shrinkage stress and debondingbehavior [62,63,64] .…”
Section: For Nanoleakagementioning
confidence: 99%